Chemical bonding-induced rich electronic properties of oxygen adsorbed few-layer graphenes. Issue 5 (18th January 2016) - Thuy Tran, Ngoc Thanh; Lin, Shih-Yang; Lin, Yu-Tsung; Lin, Ming-Fa
Abstract : The electronic properties of graphene oxides enriched by strong chemical bonding are investigated using first-principles calculations. Abstract : The electronic properties of graphene oxides enriched by strong chemical bonding are investigated using first-principles calculations. They are very sensitive to the changes in the number of graphene layers, stacking configuration, and distribution of oxygen. The feature-rich electronic structures exhibit destruction or distortion of the Dirac cone, opening of a band gap, anisotropic energy dispersions, O- and (C, O)-dominated energy dispersions, and extra critical points. All of the few-layer graphene oxides are semi-metals except for the semiconducting monolayer ones. For the former, the distorted Dirac-cone structures and the O-dominated energy bands near the Fermi level are revealed simultaneously. The orbital-projected density of states (DOS) has many special structures mainly coming from a composite energy band, the parabolic and partially flat ones. The DOS and spatial charge distributions clearly indicate the critical orbital hybridizations in O–O, C–O and C–C bonds, being responsible for the diversified properties.